A luta pelo reconhecimento de um grupo outsider do marxismo: a convergência socialista da repressão militar à expulsão do PT (1978-1992) - Mariano, Andreyson Silva (2019)
This objective research comprises the process of political organization of the Socialist Convergence, in Fortaleza, during the years of 1978 (year of its foundation), until 1992, (year of expulsion from the Workers' Party due to the so-called slogan of Fora Collor!) Also, we seek to analyze a struggle for the recognition of this political group with the Brazilian State, as a group persecuted by the military civil dictatorship. Through the Caravans as of the truth of 2013, the Brazilian State adopted Socialist Convergence as a group persecuted by the military dictatorship, with members involved in torture. We seek to carry out in this research a sociological reading that verifies or resolves the unreached socialist convergence project, its way and time, to achieve its objectives of a Brazilian Socialist Revolution. Look for this form of understanding and a collective task that interrogates our society about the democratic conquests that surpassed the military period, the groups that dispute society and redemocratize in the midst of repression. The methodology of Oral History, through interviews with former members of the C.S., documents of military repression, photographs and newspapers, analysis essays, substance and support to the body for research. A general hypothesis is that, in seeking to understand a trajectory of socialist convergence, we will find elements that have already been pointed out for the current crisis of the left in Brazil. Among them, the adaptation to parliament as an end in it and the loss of its political independence, when giving up its financial independence, with the receipt of business financing. We also studied the participation of Socialist Convergence in Fortaleza and Juazeiro do Norte, where its activists participated in electoral processes and social and political policies.